PENGGUNAAN INDEX of BIOTIC INTEGRITY (IBI) UNTUK MENILAI KUALITAS LINGKUNGAN PERAIRAN - Sukimin, Sutrisno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Historically, the health of aquatic systems was monitored primarily through chemical means. However, chemical monitoring provides only a